2013
DOI: 10.1093/pubmed/fdt037
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a culturally appropriate, community-based lifestyle intervention program for elderly Chinese immigrants with chronic diseases: a pilot study

Abstract: These promising pilot study results from this lifestyle intervention program for elderly Chinese American immigrants with chronic diseases inform the design of a more definitive trial using a randomized design and larger sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…, Lu et al . ). See Supplementary File S4 for intervention characteristics and Table for results by outcome measured.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…, Lu et al . ). See Supplementary File S4 for intervention characteristics and Table for results by outcome measured.…”
Section: Resultsmentioning
confidence: 97%
“…'s () had 93·7% African American and Lu et al . () had 100% Chinese. There were more females than males that participated in the studies apart from Chumbler et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous research found a significant association between income and poor mental health (Chung et al, 2003; Lubetkin, Jia, & Gold, 2003); the majority of our sample reported income earned less than $25,000 annually, potentially placing them at greater risk. Studies have been proposed to address depression among Asian Americans (Trinh et al, 2011; Yeung, Hails, Chang, Trinh, & Fava, 2011), and a lifestyle intervention among older Chinese immigrants saw positive changes in mental health (Lu et al, 2014). Community-based, culturally-tailored interventions and policies that address factors associated with health-related behaviors and outcomes are key to providing services to the aging Chinese community as well as other aging racial and ethnic minority communities.…”
Section: Discussionmentioning
confidence: 99%
“…Essas ações promovem mudanças fisiológicas, com melhoras significativas na saúde física e mental, como a redução da composição corporal, redução da pressão arterial sanguínea, diminuição do estresse e aumento do desempenho físico 9 . No contexto brasileiro da região Sul do Brasil, os programas que abordam a prática de atividade física ao ar livre como caminhadas ou as AMIs têm como facilitadores para a adesão, desde a manutenção e promoção da saúde física 10 , como também a gratuidade do programa 10 , a proximidade da residência 10 , socialização 11 , qualidade de vida 10 , prevenção de doenças, aprendizado de novas atividades, emagrecimento e melhora do sono 12 .…”
Section: Introductionunclassified